Evolutionary relationships of mitogenomes in a recently radiated Old World avian family - Wenqing Zang; Zhiyong Jiang; Per G.P. Ericson; Gang Song; Sergei V. Drovetski; Takema Saitoh; Fumin Lei; Yanhua Qu (Avian Research, 2023)
Environmentally heterogeneous mountains provide opportunities for rapid diversification and speciation. The family Prunellidae (accentors) is a group of birds comprising primarily mountain specialists that have recently radiated across the Palearctic region. This rapid diversification poses challenges to resolving their phylogeny. Herein we sequenced the complete mitogenomes and estimated the phylogeny using all 12 (including 28 individuals) currently recognized species of Prunellidae. We reconstructed the mitochondrial genome phylogeny using 13 protein-coding genes of 12 species and 2 Eurasian Tree Sparrows (Passer montanus). Phylogenetic relationships were estimated using a suite of analyses: maximum likelihood, maximum parsimony and the coalescent-based SVDquartets. Divergence times were estimated by implementing a Bayesian relaxed clock model in BEAST2. Based on the BEAST time-calibrated tree, we implemented an ancestral area reconstruction using RASP v.4.3. Our phylogenies based on the maximum likelihood, maximum parsimony and SVDquartets approaches support a clade of large-sized accentors (subgenus Laiscopus) to be sister to all other accentors with small size (subgenus Prunella). In addition, the trees also support the sister relationship of P. immaculata and P. rubeculoides ​+ ​P.atrogularis with 100% bootstrap support, but the relationships among the remaining eight species in the Prunella clade are poorly resolved. These species cluster in different positions in the three phylogenetic trees and the nodes are often poorly supported. The five nodes separating the seven species diverged simultaneously within less than half million years (i.e., between 2.71 and 3.15 million years ago), suggesting that the recent radiation is likely responsible for rampant incomplete lineage sorting and gene tree conflicts. Ancestral area reconstruction indicates a central Palearctic region origin for Prunellidae. Our study highlights that whole mitochondrial genome phylogeny can resolve major lineages within Prunellidae but is not sufficient to fully resolve the relationship among the species in the Prunella clade that almost simultaneously diversify during a short time period. Our results emphasize the challenge to reconstruct reliable phylogenetic relationship in a group of recently radiated species.